Hubungan pemberian MPASI sanitasi air bersih dan dukungan keluarga dengan balita stunting usia 24-59 bulan di Puskesmas Cisata Kabupaten Pandeglang - Erni Oktriyani; Meinasari kurnia Dewi; Kuswati Kuswati (THE JOURNAL OF Mother and Child Health Concerns, 2022)
Background: Stunting can cause stunted growth and development in toddlers. One of the factors related to stunting is complementary foods for breast milk, clean water sanitation and family support with stunting toddlers aged 24-59 months. Purpose: The purpose of this study was to determine the relationship between complementary feeding, clean water sanitation and family support with stunting toddlers aged 24-59 months, at the Cisata Public Health Center, Pandeglang Regency. Method: This research uses descriptive method with cross sectional approach. With a total sample of 113 people. The sampling technique in this study used total sampling. Data analysis was carried out by means of univariate and bivariate analysis using the Chi square test. Results: There was a relationship between complementary foods for breast milk (P-value=0.222 and OR=2.68), clean water sanitation (P-value = 0.276 and OR=3.1), and family support (P-value=0.294 and OR=2.68) on stunting toddlers. 24-59 months old, at Cisata Health Center Conclusion: The relationship between complementary feeding, clean water sanitation and family support with stunting toddlers aged 24-59 months, at the Cisata Public Health Center, Pandeglang Regency. Suggestion: Collaborate with local health centers and health workers to provide education about the health of stunting toddlers aged 24-59 months to mothers and families so that they can provide provisions and knowledge about stunting and can be motivated to implement good health behaviors.   Pendahuluan: Stunting dapat menyebabkan hambatan pertumbuhan dan perkembangan pada balita. Salah satu faktor yang berkaitan dengan stunting adalah MP ASI, sanitasi air bersih dan dukungan keluarga dengan balita stunting usia 24-59 bulan. Tujuan: Tujuan penelitian ini adalah untuk mengetahui hubungan pemberian MPASI,Sanitasi Air Bersih dan Dukungan Keluarga Dengan Balita stunting usia 24-59 bulan, di  Puskesmas Cisata Kabupaten Pandeglang. Metode: Penelitian ini menggunakan metode Deskriptif dengan pendekatan Cross sectional. Dengan jumlah sampel sebanyak 113 orang Teknik Pengambilan sampel pada penelitian ini menggunakan total sampling. Analisa data dilakukan dengan cara analisa univariat dan bivariat menggunakan uji Chi square. Hasil: Ada hubungan antara MPASI  (P-value=0.222 dan OR=2.68), sanitasi air bersih (P-value = 0.276 dan OR=3.1), dan dukungan keluarga (P-value=0.294 dan OR=2.68) terhadap balita stunting usia 24-59 bulan, di Puskesmas Cisata. Kabupaten Pandeglang tahun 2022. Simpulan: Hubungan pemberian MPASI,Sanitasi Air Bersih dan Dukungan Keluarga Dengan Balita stunting usia 24-59 bulan, di  Puskesmas Cisata Kabupaten Pandeglang. Saran: Bekerja sama dengan puskesmas maupun tenaga kesehatan setempat untuk memberikan edukasi mengenai kesehatan balita stunting usia 24-59 bulan  kepada ibu dan keluarga sehingga dapat memberikan bekal dan pengetahuan mengenai stunting dan dapat termotivasi melaksanakan perilaku kesehatan yang baik.